Diet composition of Korean water deer (Hydropotes inermis argyropus) from the Han River Estuary Wetland in Korea using fecal DNA - Kim, Jihee; Joo, Sungbae; Park, Sangkyu (Mammalia, 2021)
To investigate the foraging preferences of the Korean water deer (Hydropotes inermis argyropus) from the Janghang wetlands located in Han River estuary in South Korea, we elucidated their diet compositions using DNA extracted from their fecal samples. Samples were collected from the Janghang wetlands from June 2013 to January 2015. For dietary analysis, we amplified the internal transcribed spacer 2 (ITS2) and the large subunit of ribulose-1,5-bisphosphate carboxylase (rbcL) regions, followed by cloning and sequencing. We were able to detect 20 families and 35 genera of plants from 77 fecal samples, showing that water deer in the Janghang wetlands mainly preferred Salicaceae (27.5%), Fabaceae (17.5%), and Poaceae (14.2%). In winter, the relative frequency of woody plant detection (81.3%) was much higher than that in other seasons. Our results suggest that Korean water deer in Janghang wetlands browse or graze depending on the locally-available plants species in their habitat as intermediate feeders. Non-invasive approaches using fecal samples could be applied to study food webs of various species and ecosystems for conservation and management of wildlife.
Keywords: dietary analysis; feces; Hydropotes inermis argyropus; Korean water deer; non-invasive approach